Rekonstruksi Alat Skrining Diskalkulia untuk Siswa Sekolah Dasar - Nikmah Sofia Afiati; Saifuddin Azwar (Faculty of Psychology, Universitas Gadjah Mada, 2016)
Result of some studies reported that 3%-14% of school age students arediagnosed as dyscalculia. The early step to diagnose children with dyscalculia is by usinga screening test. The construction of the screening test by previous researchers has notbeen able to result a satisfactory tool. This study aims to reconstruct the dyscalculiascreening tool (TSD/Tes Skrining Diskalkulia), which developed in order to determineelementary school students that risk for dyscalculia. The participants were 367 studentsfrom 1 st to 4 th grade selected from 5 different school in Magelang Regency. Result showedthat the new structure of the dyscalculia screening tool has a good content validity andconstruct validity. This tool also has good reliability which is 0.864 with low standarderror of measurement. It showed that 69 items that are constructed has good psychometricproperties.